If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Sin(3x) + sin(9x) = 0 Remove parenthesis around (3x) inS * 3x + sin(9x) = 0 Reorder the terms for easier multiplication: 3inS * x + sin(9x) = 0 Multiply inS * x 3inxS + sin(9x) = 0 Remove parenthesis around (9x) 3inxS + ins * 9x = 0 Reorder the terms for easier multiplication: 3inxS + 9ins * x = 0 Multiply ins * x 3inxS + 9insx = 0 Reorder the terms: 9insx + 3inxS = 0 Solving 9insx + 3inxS = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '3inx'. 3inx(3s + S) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'inx' equal to zero and attempt to solve: Simplifying inx = 0 Solving inx = 0 Move all terms containing i to the left, all other terms to the right. Simplifying inx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(3s + S)' equal to zero and attempt to solve: Simplifying 3s + S = 0 Reorder the terms: S + 3s = 0 Solving S + 3s = 0 Move all terms containing i to the left, all other terms to the right. Add '-1S' to each side of the equation. S + -1S + 3s = 0 + -1S Combine like terms: S + -1S = 0 0 + 3s = 0 + -1S 3s = 0 + -1S Remove the zero: 3s = -1S Add '-3s' to each side of the equation. 3s + -3s = -1S + -3s Combine like terms: 3s + -3s = 0 0 = -1S + -3s Simplifying 0 = -1S + -3s The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 9-y=15-5y | | 7-y=3-3y | | Sin(4x)cos(2x)= | | 4+3y=5y | | y=3x^2-17x+10 | | x*ln((8*x^3))+ln((8*x^2))=20-ln(2) | | 72=-16x^2+64x+12 | | 1x=8y+48 | | 2x/2-3x | | 0=-16x^2+64x+8 | | 2(f-3)=f+5 | | 100=60a+[40(2a)] | | -9=x(-10/x) | | 18x+6x-4x+2=2x-10x+16 | | 5x+5=4y-23 | | 2/7*3/8 | | Y-2=5(x-1)/3 | | 18-2x=12-5x | | y+w=c | | x^4y^2-4x^2y=0 | | 3x-3y-x^2y=0 | | 3p-7=14 | | 2x-4+45=4x | | 9-1.84= | | 2x-4=8x-2 | | 12/75 | | (11/3)/(3/2) | | x^2+2y^2+3xy=15 | | 2x-e=-5 | | 20x/x^2 | | 4x+8-x-3=2 | | 110=-5x |